2018
DOI: 10.1007/s12072-018-9874-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liver function using gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid enhanced magnetic resonance imaging based on a three-dimensional volumetric analysis system

Abstract: BackgroundMagnetic resonance imaging with gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (EOB-MRI) is a diagnostic modality for liver tumors. Three-dimensional (3D) volumetric analysis systems using EOB-MRI data are used to simulate liver anatomy for surgery. This study was conducted to investigate clinical utility of a 3D volumetric analysis system on EOB-MRI to evaluate liver function.MethodsBetween August 2014 and December 2015, 181 patients underwent laboratory and radiological exams as standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, a volumetric determination can also be performed with MRI data, as shown in the study by Ippolito et al ( 55 ). Kudo et al opted for a more sophisticated approach using a 3D volumetric analysis system ( 63 ). By using a semiautomatic approach and an image processing algorithm, they extracted the liver and spleen parenchyma by placing volumes of interest; the resulting extracted 3D volumes allowed measurement of the average SI and determination of the liver-to-spleen ratio.…”
Section: Recent Approaches To Liver Function Measurement Using Contra...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a volumetric determination can also be performed with MRI data, as shown in the study by Ippolito et al ( 55 ). Kudo et al opted for a more sophisticated approach using a 3D volumetric analysis system ( 63 ). By using a semiautomatic approach and an image processing algorithm, they extracted the liver and spleen parenchyma by placing volumes of interest; the resulting extracted 3D volumes allowed measurement of the average SI and determination of the liver-to-spleen ratio.…”
Section: Recent Approaches To Liver Function Measurement Using Contra...mentioning
confidence: 99%
“…Nevertheless, the rrT1 must still be calculated manually; thus, there is a demand for software solutions to establish the rrT1 value as a liver function parameter, ideally in prospective trials. In addition, 3D volumetry for the liver is not yet fully automated; however, various software solutions for 3D volumetry are available on the market, one of which was successfully used by Kudo et al ( 63 ) to semiautomatically determine the liver-to-spleen ratio. As in this case, semiautomatic or manual approaches are mostly used for volume determination.…”
Section: Recent Approaches To Liver Function Measurement Using Contra...mentioning
confidence: 99%
“…For the assessment of liver function on gadoxetic acid-enhanced HBP-MRI, spleen SI has been commonly used as an internal reference for normalizing liver SI [ 7 8 9 28 ]. However, LSSR is influenced by MRI parameters, which can hinder the use of this index in clinical practice when HBP-MRI is performed using various scanning parameters.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thus, the uptake and excretion of Gd-EOB-DTPA offers the potential for quantifying regional liver function, and several studies have suggested that the low signal intensity of liver parenchyma on EOB-MRI in the hepatobiliary phase reflects a poor liver function. 11,12 With EOB-MRI using a 3-dimensional (3D) volumetric analysis system, it is possible to evaluate signal intensity of specific liver regions. 11 Hence, this technique allows preoperative evaluation of the function of the future remnant liver region, by assessing the signal intensity of the proposed remnant liver separately from the resected region.…”
Section: Introductionmentioning
confidence: 99%